Basin analysis of the Katangan Basin of Zambia: subsidence mechanisms, dynamic stratigraphy, and mineral systems - Purkiss, M (2023)
The Neoproterozoic Katangan basin of Central Africa represents the largest sediment-hosted copper province on Earth, recording ∼300 Myr of sedimentation. This work applies a basin analysis approach to understanding the basin’s evolution in Zambia, combining facies analysis, sequence stratigraphy, and subsidence analysis.